Polemical pain : slavery, cruelty, and the rise of humanitarianism - Abruzzo, Margaret Nicola (New studies in American intellectual and cultural history., 2011)
" ... Shows how the debate over slavery's cruelty played a large, unrecognized role in shaping moral categories that remain pertinent today"--Jacket, page [3].